Ten lessons of leadership: reflections of a female academic. Issue 11 (November 2020) - Gilbert, F.J.
Abstract : The defining qualities and characteristics of a good leader — visionary, decisive, clear communicator, honesty and integrity, commitment and passion, being inspirational, accountable, well organised with the ability to delegate and empower—have been well documented. There are many articles with advice on how to lead, and there are excellent courses on leadership. In this article, I would like to explore how the general advice pertains to academia (and an academic radiologist), and whether this advice is relevant and whether the principles of leadership are the same. I have reflected on my own career and I have come up with my own 10 lessons of leadership that I have learnt over my working life. There are elements of leadership that are common across different sectors of business and healthcare, and examining how these are relevant to academia can be illuminating. Highlights: Academic leaders are visionary, inspirational and clear communicators. Integrity, commitment and passion are characteristics of an academic leader. Academic leaders are decisive, accountable, well organized and delegate. Ten lessons of leadership – invest in quality, work hard, apologise and have fun. Senior female academics bring valued diversity to an organisation.